-x+6=-11

Simple and best practice solution for -x+6=-11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -x+6=-11 equation:


-x+6=-11

We simplify the equation to the form, which is simple to understand
-x+6=-11

We move all terms containing x to the left and all other terms to the right.
-1x=-11-6

We simplify left and right side of the equation.
-1x=-17

We divide both sides of the equation by -1 to get x.
x=17

See similar equations:

| -4(4x+2)=37-7x | | 6z-4z+11=7 | | -79-12x=-4x+89 | | -54=16+y | | 2x+6=20+x | | 4x-9=3x+14 | | 0.5x+7=0.75-4 | | -54=15+y | | -26+7x=10x+10 | | [t+9]-8=5 | | 8x+4-2=-5+4x | | x^2+12=-8x | | Y=30+0.85Y+20+40 | | 4/6=238/x | | x+15=-21 | | 5x-52=11x+44 | | 22/16x+50=128 | | -3x-4=8x+7 | | 1/5x-9=-9 | | v=2nr | | 3x+7x-2=6 | | 70+25w=200 | | 1/2y-2/3=7/8 | | 1-4b+2-5b= | | 125=50+.50b | | 12(4/(1/3))=x | | 12m=276 | | 15-7x=18-6x | | x/2+1/4+3/4 | | x=.4+.2y | | 12*(4/1/3)=x | | -0.09m+-22m= |

Equations solver categories